An enhanced vertical handover scheme for monitoring applications - Ibrahim, Hatem F. H. (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
For service providers around the world, the network is the strategic platform for delivering new and advanced services to many end-user devices. Nowadays, the need of using two networks at the same time is increasing sharply especially in security monitoring systems. The switching between networks means handoff from one network to another and this is called vertical handover. Integration of various networks such as GPRS and WLAN into IP-based networks is required in these kinds of services, which further requires a seamless vertical handoff between wireless networks. However, all current vertical handover algorithms are implemented without taking into consideration the effect of any signal interfering that might occur, such as jamming signals that will confuse the handoff decision whether it should be taken or not. An improved GPRS-WLAN vertical handover is proposed in this research work. This algorithm is implemented with taking into consideration that the handover decision occurs depending on the received signal strength indicator (RSSI) as well as the network throughput in order to get high service quality as well as seamless network connection. Due to the tunneling that have been proposed in this algorithm, a significant reduction in the handover delay has been achieved. Finally, as a conclusion, all the objectives of this research work is achieved which proves that when the network handoff depends on the throughput as well as the RSSI, is much better when the handoff depending on the RSSI only as the service connection will be continuous with the same quality or better.